ENTREPRENEURIAL MARKETING: CONCEPTUALIZATIONS, DIMENSIONAL PECULIARITIES AND RESEARCH INSTRUMENTATION - Osuagwu, Linus (Journal of Business And Entrepreneurship, 2022)
Marketing and entrepreneurship are interrelated business activities. The entrepreneurial marketing construct has been associated with myriad of conceptualizations. Generally, entrepreneurial marketing is a creative, mainly unstructured, and vital practice for marketing decision-makers to achieve business efficiency and effective within their relevant contextual settings of operations. It is concerned with doing something new with ideas, goods, services, processes, or technology and refining these ideas, goods, services and processes to market segments and environments of interest in order to meet the market needs, demands, and opportunities in a new or different way. This means that entrepreneurial marketing is an innovative and creative process of marketing goods, services, and ideas to target market segments and environments of interest that have been hitherto unexploited. This conceptual paper synthesizes materials from relevant extant literature to conceptualize the entrepreneurial marketing construct, presents its dimensional peculiarities, and proposes a research agenda (with a research instrument) to investigate the construct in different business and cultural settings. The paper has theoretical and practical forms of values, especially when situated within different cultural (developed and developing countries) and business contexts (small and large business organizations).